Analysis of Income From Virginia Tobacco Farming GL26H Variety Using The Slicing Technique in Keruak District: Analisis Pendapatan Usahatani Tembakau Virginia Varietas GL26H Dengan Teknik Rajangan Di Kecamatan Keruak - Muaziz Sabri; Rini Endang Prasetyowati; Muhammad Joni Iskandar; Muhammad Anwar (Jurnal Ilmiah Manajemen Agribisnis, 2026)
The GL26H variety is a type of virginia tobacco developed on Lombok Island. The purpose of this study was to determine the income of the GL26H virginia tobacco farming business using the shredding technique with a partnership pattern. The method used was descriptive quantitative, the research location was selected purposively with data collection techniques through questionnaires. The number of respondents was 40 people determined by quota sampling, while sampling was carried out by snowball sampling. Data were analyzed using cash flow analysis techniques. The results of the study showed that the GL26H virginia tobacco farming business using the shredding technique in Keruak District for one planting season had an average production cost of IDR 73,616,894/LLG or IDR 61,509,057/Ha, revenue of IDR 113,172,990/LLG or IDR 94,310,825/Ha, and income of IDR 39,556,096/LLG or IDR 32,801,768/Ha.